Political Impetus: Towards a Successful Agenda-Setting for Inclusive Health Policies in Low- and Middle-Income Countries; Comment on "Shaping the Health Policy Agenda: The Case of Safe Motherhood Policy in Vietnam" - Xiaoguang Yang; Xu Qian (Kerman University of Medical Sciences, 2016)
Agenda-setting is a crucial step for inclusive health policies in the low- and middle-income countries (LMICs). Enlightened by Ha et al manuscript, this commentary paper argues that 'political impetus' is the key to the successful agenda-setting of health policies in LMICs, though other determinants may also play the role during the process. This Vietnamese case study presents a good example for policy-makers of other LMICs; it offers insights for contexts where there are limited health resources and poor health performance. Further research which compares various stages of the health policy process across countries, is much needed.